Clotting Activation after Transjugular Intrahepatic Portosystemic Stent Shunt - Basili, Stefania; Manuela, Merli; Ferro, Domenico; Lionetti, Raffaella; Rossi, Elisabetta; Riggio, Oliviero; Valeriano, Valentina; Capocaccia, Livio; Violi, Francesco (Thrombosis and Haemostasis, 1999)
Background and Aim. Aim of the study was to investigate the behaviour of clotting system in peripheral circulation of cirrhotic patients undergoing transjugular intrahepatic portosystemic stent shunt (TIPS). Methods. Clotting variables and endotoxemia were measured 48 h and 30 days after TIPS in patients randomised to receive heparin or not. Results. Forty-eight hours after TIPS, a significant increase of prothrombin fragment F1+2 was observed; such increase was less evident in patients given heparin. Similar findings were observed for endotoxemia, which, however, was not affected by heparin treatment. Thirty days after TIPS procedure prothrombin fragment F1+2 and endotoxemia returned to baseline values independently of the treatment given. Conclusion. This study shows that TIPS is associated with an increase of clotting activation which might contribute to acute thrombosis observed after this procedure.